Social-Pedagogical Perspectives Of The Development Of Primary Schoolchildren’s Ability Of Self-Esteem - Hakobyan, Greta (Զանգակ հրատ.)
The article discusses methodological matters related to the ability of self-esteem in the primary school age. The factors for and methods of the development of the ability of self-esteem in the teaching process as well as the potential of school subjects have been analysed. Surveys have been conducted among teachers concerning their engagement in the development of schoolchildren’s self-esteem and a sample lesson has been designed for developing the ability of self-esteem at school.
Keywords: Pedagogy